Determinants of student's loyalty in the Malaysian private higher education industry - Lee, Lai Meng (2017)
The competitive private higher education industry in Malaysia indicates that the profitability and the viability of private higher education institutions (Private HEIs) are compromised by uncertain levels of students’ loyalty. The objectives of this study were fourfold: (a) to determine the level of students’ loyalty in Private HEIs in Malaysia, (b) to determine the relationships between service quality (academic quality, program quality and administrative quality), reputation (university management and academic and media reputation), relationship benefits and students’ loyalty, (c) to determine the significant effects of the independent variables on students’ loyalty and lastly, (d) to determine the mediating effects of satisfaction on these relationships. This quantitative cross sectional study used the proportionate stratified sampling design. 400 students from various Private HEIs participated in this study. The data was collected via a personally administered questionnaire and was analysed using various statistical techniques such as correlation, multiple regression and mediation analyses. This study found that the loyalty levels of students in Malaysian Private HEIs are moderate. All the independent variables have positive relationships with students’ loyalty. Empirical evidence concludes that administrative quality, university management and relationship benefits have significant effects on students’ loyalty, whilst academic quality, program quality and academic and media reputation did not. Satisfaction was found to mediate the relationship between all the independent variables and students’ loyalty. The main significance of this study is the empirical confirmation of the positive direct effect of relationship benefits on students’ loyalty and the mediating effect of satisfaction on this relationship in the Malaysian private higher education context. The findings in this study can be used by managers of Private HEIs in Malaysia for managing their students’ loyalty.